The Effects of Levetiracetam on Neural Tube Development of Chick Embryos. Issue 4 (November 2015) - Yaldiz, Can; Ceylan, Davut; Sayin, Murat; Kaçira, Tibet; Dilek, Fatma H.
Abstract : Purpose: This study aims to demonstrate the effects of therapeutic and high doses of Levetiracetam on neural tube development in early-stage chick embryos. Materials and Methods: The embryos were divided into 3 groups: control (n=20), treatment (n=20), and high-dose Levetiracetam (n=20). After 24 hours of incubation, the eggs were opened under ×4 optical magnification. The control group dosed by0.045 mL normal saline, the treatment group dosed by 0.045 mL normal saline with 4.5 μL Levetiracetam, and the high-dose group dosed by 0.045 mL normal saline with 45 μL Levetiracetam. At the end of 72 hours, all eggs were opened and the embryos were taken out for hematoxylin and eosin and immunohistochemistry (Bcl-2, Bax) stainings in order to examine microscopically and macroscopically. Results: Fifty-seven of 60 incubated embryos were evaluated. Neural tube closure was found in all embryos in all of the 3 groups (examined with hematoxylin and eosin and Bcl-2 and Bax) and no pathologic findings were detected. The development of chorda dorsalis, dorsal aorta, mesenchymal connective tissue, crista neuralis, and the somites were compatible for up to 72 hours. Microscopical examination showed that Levetiracetam causes no neural tube closure defects in the treatment or high-dose Levetiracetam groups. Conclusions: The apopytotic process was normal and no neural tube closing defects occurred with the used therapeutic agent, even when high doses were performed. It has been derived that Levatiracetam can be used as a safe antiepileptic drug in pregnant women.